A review of studies on green finance of banks, research gaps and future directions. (2nd October 2022) - Akomea-Frimpong, Isaac; Adeabah, David; Ofosu, Deborah; Tenakwah, Emmanuel Junior
ABSTRACT: With growing global concern for environmental protection, climate change and sustainable development, policymakers and researchers have recently focused on green finance. In this study, existing studies on green finance in the context of the banking sector have been reviewed with considerations on products and determinants of green finance. The content analysis approach has been used to critically analyse and summarize forty-six (46) relevant studies. The results found green securities, green investments, climate finance, carbon finance, green insurance, green credit and green infrastructural bonds as part of key green finance products of banks. Pertinent determinants the study found to be influencing green finance policies from banks include environmental and climate change policies, interest rates, religion, risks, social inclusion and social justice as well as banking regulations. In theory, this study provides a guide for further studies. The results of the study will assist banks on the key issues to consider in adopting, developing and granting green finance.